Characteristics, causes, and price effects: Empirical evidence of intraday Edgeworth cycles - Manuel Siekmann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
Edgeworth cycles represent the leading concept to explain observed pricing patterns on retail gasoline markets and have been subject to numerous empirical investigations on an interday level. In this paper, I present unique evidence of the presence, causes, and price effects of intraday Edgeworth-type cycles for an entire OECD country, using high-frequency price data from German gasoline stations. I find vast evidence of intraday cycles across municipalities in Germany. Cycle asymmetry and intensity is stronger in more concentrated markets and decreases with a higher share of non-major brands. My analysis suggests that intraday cycles are a sign of competition with a price decreasing effect during evening hours, where consumers conscious of their purchase timing can benefit most.
Keywords: L11; L71; 330; Gasoline Markets; Fuel Prices; Edgeworth Cycles; Intraday Pricing